RESEARCH SKILLS, PRODUCT MAKING SKILLS, AND STUDENTS' PROCEDURAL KNOWLEDGE ON BIOLOGICAL LEARNING USING ENGINEERING DESIGN PROCESS (EDP) - Husna Dita Rahmah (Jurnal Pengajaran MIPA, 2021)
Nowadays, Human resources in Indonesia need more skills to succeed in facing the competition in the 21st century. One of the skills that must have is research and product-making skills. This study aimed to analyze students' research skills, product-making skills, and procedural knowledge in learning biology, especially the concept of food processing technology using the Engineering Design Process (EDP). EDP is a learning approach through idea, design, creation, and test activities skills to develop STEM-based learning that can strengthen research and product skills. This study used a quasi-experimental method with a non-equivalent control group research design. The research sample consisted of 24 EDP and 21 students in non-EDP classes. Data was collected using a rubric to measure research and product-making skills—also multiple choice questions to measure students' procedural knowledge. The results of this study indicated that EDP learning strengthened the research skills of students in EDP classes, especially the skill of determining the topic of problems, determining tools and materials, and making product designs. On the other hand, students in non-EDP classes are better at determining the research variables and making hypotheses. Students in EDP classes outperformed all indicators of skills in making products. EDP learning strengthened students' product-making skills in selecting, packaging, and making packaging on food products. Likewise, procedural knowledge, especially on indicators determining the research variables.